Hubungan Politik dan Dakwah - Day, Syamsul Bachri (FIkom Unisba, 2005)
Nowadays, da’wah and politics were seen as two distinct areas. Such opinion proved to be disadvantage because both politics and da’wah are essentially interrelating each other in a functional matter, even organics. In Islam, men are constituted as khalifah, or leader of the universe in order to manifest Allah’s will. Equipped with religious principles, dynamic and creativity, along with ratio and amanah, it is the task of men to overcome every challenge. There are two kinds of politics in the world of Islam: high politics (high quality of politics) and low politics (low quality of politics). High politics covered some principles, e.g.: politics as amanah, accountable, brotherhood. Meanwhile, low politics was characterized by violence, brutality, meanness, total submission, and unethical political interactions all of this remind us with Macchiavelian style of politics. Islam only addressed high politics in its practice for the good of society.